FOURRIER TRANSFORM INFRA-RED (FT-IR) SPECTROSCOPY DAN KEKUATAN TARIK SERAT KULIT BATANG MELINJO MENGGUNAKAN MODIFIKASI DISTRIBUSI WEIBULL - Chandarabakty, Sri (Jurnal MEKANIKAL, 2014)
Abstract: Fourrier Transform Infra-Red (FT-IR) spectroscopy and Tensile Strength of Melinjo Leather Fiber Using Modified Weibull Distribution. This study aims to analyze the influence of surface treatment on the chemical properties of the fiber stem (bast fiber) â€œmelinjoâ€ (Gnetum gnemon) and its relation to the mechanical properties of the fiber. The research process begins with providing surface treatment on fiber rods gnetum gnemon, namely boiling the water for 3 hours of media and media NaOH 5% respectively for 2 and 3 hours. Then the fiber surface morphology observed using Scanning Electron Microscopy (SEM), further testing of FT-IR is useful to re-characterization of the chemical changes that occur in the fiber caused by the treatment given. The results of these observations are then compared with the value of bark fiber tensile strength gnetum gnemon analyzed using a modified Weibull distribution. CH at 2900 cm-1 was seen in all types of fibers and the highest intensity seen in the media treatment of the fiber with water 3 hours. Group C = O (carbonyl) at 1735 cm-1 is only seen in fibers with boiled treatment for 180 hours. C-OH group at 1239 cm -1 peak decreases as the duration of treatment. Of physical and mechanical properties of the fiber, the fiber surface treatment on stem gnetum gnemon not only look at the surface topography but also on the distribution of fiber diameter and fiber strength were analyzed by two-parameter Weibull distribution model. Â Keywords: Fourrier Transform Infra Red (FT-IR), melinjo leather fiber, Weibull Distribution